Studi Peningkatan Output Modul Surya Dengan Menggunakan Reflektor - Sidopekso, Satwiko; Febtiwiyanti, Anita Eka (BERKALA FISIKA, 2010)
Efforts to optimize the power output of solar modules using a mirror. In this study used 2 pieces of flat mirrors as solar reflectors mounted on the right and left of the solar module. Measurement is done by directing the position of solar modules in order to obtain optimum results with a corner reflector 50 0, 600, 700. Based on the measurement results, we obtained at maximum power cost solar modules using the corner reflector 600. The increase in power output compared to 92.7% without using a reflector. Â Keywords:Â reflector, solar module, output power